Analysis of Obstacles to Policy Handling Profiteering Support for Political Party Membership at the Registration Stage Candidates for the 2024 Election in the City of Tanjung Balai - Tanjung, Yuhendra; Bengkel Ginting; Indra Fauzan (Universitas Medan Area, 2023)
This research endeavors to delve into the intricacies that impede the effective implementation of policies designed to counter profiteering support for political party membership during the pivotal registration phase for candidates in the upcoming 2024 general election in the City of Tanjung Balai. Employing a meticulous descriptive qualitative method, the study unfolds in the unique context of Tanjung Balai, North Sumatra Province. The primary focus is on the nuanced execution of policies aimed at handling profiteering support for political party membership during both the registration and verification stages for candidates participating in the 2024 election within the city. The research methodology integrates multifaceted approaches, including in-depth interviews with seven knowledgeable informants, rigorous document analysis, and a thorough examination of relevant literature. Through this comprehensive exploration, the study seeks to unravel the multifarious challenges and obstacles inherent in the implementation of policies addressing profiteering support for political party membership, shedding light on the intricate dynamics of the political landscape.